ATG5 is required for B cell polarization and presentation of particulate antigens. Issue 2 (1st February 2019) - Arbogast, Florent; Arnold, Johan; Hammann, Philippe; Kuhn, Lauriane; Chicher, Johana; Murera, Diane; Weishaar, Justine; Muller, Sylviane; Fauny, Jean-Daniel; Gros, Frédéric
ABSTRACT: The involvement of macroautophagy/autophagy proteins in B-cell receptor (BCR) trafficking, although suspected, is not well understood. We show that ATG5 (autophagy related 5) contributes to BCR polarization after stimulation and internalization into LAMP1 (lysosomal-associated membrane protein 1) + and major histocompatibility complex class II (MHC-II) + compartments. BCR polarization is crucial in the context of immobilized antigen processing. Moreover, antigen presentation to cognate T cells is decreased in the absence of ATG5 when the model antigen OVAL/ovalbumin is provided in an immobilized form in contrast to the normal presentation of soluble OVAL. We further show that ATG5 is required for centrosome polarization and actin nucleation in the immune synapse area. This event is accompanied by an increased interaction between ATG16L1 (autophagy related 16-like 1 [ S. cerevisiae ]) and the microtubule-organizing center-associated protein PCM1 (pericentriolar material 1). In the human B cell line BJAB, PCM1 is required for BCR polarization after stimulation. We thus propose that the ATG12 (autophagy related 12)–ATG5-ATG16L1 complex under BCR stimulation allows its interaction with PCM1 and consequently facilitates centrosome relocalization to the immune synapse, optimizing the presentation of particulate antigens. Abbreviations: ACTB: actin beta; ACTR2/3: ARP2/3 actin-related protein 2/3; APC: antigen-presenting cells; ATG: autophagy-related; BCR: B cell receptor; BECN1/Beclin 1: beclin 1, autophagy related; CDC42: cell division cycle 42; Cr2: complement receptor 2; CSFE: carboxyfluorescein succinimidyl ester; DAPI: 4ʹ, 6-diamidino-2-phenylindole dihydrochloride; EEA1: early endosome antigen 1; ELISA: enzyme-linked immunosorbent assay; FITC: fluorescein isothyocyanate; GC: germinal center; GJA1/CX3: gap junction protein, alpha 1; Ig: immunoglobulin; LAMP1: lysosomal-associated membrane protein 1; LAP: LC3-associated phagocytosis; LM: littermate; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAPK/ERK: mitogen activated protein kinase; MHC-II: major histocompatibility complex class II; MIIC: MHC class II compartment; OVAL: ovalbumin; PBS: phosphate-buffered saline; PCM1: pericentriolar material 1; PtdIns3K: phosphatidylinositol 3-kinase; PTPRC/CD45RB/B220; Protein tyrosine phosphatase, receptor type, C; SYK: spleen tyrosine kinase; TBS: Tris-buffered saline; TCR: T cell receptor; ULK1: unc-51 like kinase 1